Mechanisms Maintaining Biomass Stability in Woody Species Communities in Evergreen Broadleaved Forests of Dong Nai Culture and Nature Reserve, Dong Nai province, Southern Vietnam - Van Quy, Nguyen; Cuong, Le Van; Manh, Vu; Van, Nguyen Thi; Hop, Nguyen Van; Tuan, Nguyen Thanh; Hai, Nguyen Hong (Journal of Forestry Science and Technology, 2024)
Tropical forest ecosystems experience dynamic changes in response to environmental fluctuations and disturbances. Understanding the mechanisms governing their stability is crucial for maintaining ecosystem services. Among these ecosystems, evergreen broadleaved forests play a pivotal global role. This study investigates the impacts of overyielding, stand structure, species asynchrony, and the stability of dominant species on community biomass stability (CBS) within the Dong Nai Culture and Nature Reserve's evergreen broadleaved forests. The study utilized species richness, diameter-at-breast-height (DBH) variation coefficient, species asynchrony, and stability of dominant species as explanatory variables. The response variables included CBS, mean biomass (µ), and biomass standard deviation (σ). Three structural equation models (SEMs) were constructed to assess the relative strengths of direct and indirect effects among these variables. The results indicated that: (1) The SEMs achieved a good fit, explaining 41.8% of the variance in CBS. (2) Species richness negatively correlated significantly with µ (path coefficient = -0.112) and σ (-0.056). (3) DBH variation coefficient showed significant negative correlations with CBS (-0.161) and µ (-0.087). (4) Species asynchrony exhibited significant positive correlations with CBS (0.061), µ (0.076), and σ (0.061). (5) Dominant species stability showed significant positive correlations with CBS (0.588) and µ (0.153) and a negative correlation with σ (-0.588). These findings underscore that while stand structure and species asynchrony significantly influence CBS in evergreen broadleaved forests, the stability of dominant species emerges as the primary predictor of CBS. Therefore, effective forest management strategies should prioritize conserving and enhancing conditions that support dominant species, ensuring the sustainability of forest ecosystems in the study area.